2011
DOI: 10.2298/avb1104429d
|View full text |Cite
|
Sign up to set email alerts
|

Environmental prevalence and persistence of Listeria monocytogenes in cold-smoked trout processing plants

Abstract: The presence of Listeria monocytogenes on the surfaces of equipment and worker’s hands during different production stages, as well as on fish skin and meat during processing and storage of cold-smoked trout, was investigated. Listeria monocytogenes was recovered from 10 (6.06%) of a total 165 cotton-swabbed samples collected from the surfaces of equipment and worker’s hands at two separate processing facilities. Of 105 samples collected from fish skin and meat during various production steps in both pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[ 27 ] and Dimitrijevíc et al . [ 14 ] have been demonstrating that the prevalence of L. monocytogenes in the environment of cold-smoked trout processing plants ranges from 6.06%–30%. Moreover, Kovačević et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 27 ] and Dimitrijevíc et al . [ 14 ] have been demonstrating that the prevalence of L. monocytogenes in the environment of cold-smoked trout processing plants ranges from 6.06%–30%. Moreover, Kovačević et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability of this bacterium to survive and grow under anaerobic conditions as well refrigerator temperatures, and its high tolerance to salt, allows it to thrive in food processing environments [ 11 , 12 ]. Especially in meat, dairy and seafood processing plants is L. monocytogenes commonly isolated from the food processing environment where it can exist in biofilms [ 9 , 10 , 13 , 14 , 15 ]. These biofilms can occur on food handling or food processing surfaces (e.g., cutting boards, slicing blades, conveyer belts and stainless steel equipment) or in food processing or storage areas (e.g., drains, ventilation, floors, refrigerators) [ 9 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidance of postprocessing contamination requires effective employee training programs, prerequisite programs, sanitation standard operating procedures, and appropriate environmental monitoring programs. Persis tence of L. monocytogenes in food processing environments for months or years has been identified as one of the most important sources of L. monocytogenes cross-contamination of finished products (4,10,30). Because L. monocytogenes strains can persist in food production plants for multiple years (2 4 ,3 3 , 3 7 ,3 9^fl, 48), active strategies such as " seek & destroy" (6) are necessary to control persistent L. monocytogenes.…”
mentioning
confidence: 99%
“…Samples have been taken from incoming (raw) materials, meal components and final products as well from the environment, because environmental sources may, under conditions of poor cleaning and sanitation, harbor pathogenic micro-organisms such as L. monocytogenes or serve as vehicles for cross-contamination (Lianou & Sofos, 2007). Especially, non-food contact surfaces, such as floor drains and cold floors, have a higher prevalence of L. monocytogenes in comparison with food contact surfaces such as slicers and utensils (Carpentier & Cerf, 2011;Dimitrijevíc et al, 2011;Hoelzer et al, 2011). In this case study, the pathogen was not found in the environmental samples.…”
Section: Discussionmentioning
confidence: 99%